Assessment of different pedestrian communication strategies for improving driver behavior at marked crosswalks on free channelized right turns. (February 2023) - Almukdad, Abdulkarim; Muley, Deepti; Alfahel, Radwan; Alkadour, Firas; Ismail, Reem; Alhajyaseen, Wael K.M.
Highlights: Drivers yielding behavior was tested using four gestures with 5419 observations. Overall 13.84% drivers yielded to confederates. Confederate's and driver's gender affected probability of yielding. Gestures utilized had significant effect on yielding behaviour. Drivers with slower approach speed had 2.8 times higher probability of yielding. Abstract: Introduction: Previous studies have indicated low driver yielding rates to pedestrians in various countries. This study analyzed four different strategies to improve driver yielding rates at marked crosswalks on channelized right turn lanes at signalized intersections. Method: A sample of 5, 419 drivers was collected for four gestures using field experiments for males and females in the State of Qatar. The experiments were conducted in daytime and nighttime on weekends at three different locations; two sites are located in an urban area and the third is located in non-urban area. The effect of pedestrians' and drivers' demographic characteristics, gestures, approach speed, time of the day, location of the intersection, car type, and driver distractions on yielding behavior is investigated using logistic regression analysis. Results: It was found that for the base gesture, only 2.00% of drivers yielded to the pedestrians, while for hand, attempt, and vest-attempt gestures the yielding percentages were considerably higher, 12.81%, 19.59%, and 24.60%, respectively. The results also showed that females received significantly higher yielding rates compared to males. In addition, the probability of a driver yielding increased 2.8 times when drivers approached at slower speed compared to a higher speed. Further, drivers' age group, accompanied, and distractions were not significant in determining drivers' probability of yielding.